2014
DOI: 10.1038/onc.2014.370
|View full text |Cite
|
Sign up to set email alerts
|

SOX30, a novel epigenetic silenced tumor suppressor, promotes tumor cell apoptosis by transcriptional activating p53 in lung cancer

Abstract: Although members of SOX family have been well documented for their essential roles in embryonic development, cell proliferation and disease, the functional role and molecular mechanism of SOX30 in cancer are largely unexplored. Here, we first identified SRY-box containing gene 30 (SOX30) as a novel preferentially methylated gene using genome-wide methylation screening. SOX30 hypermethylation was detected in 100% of lung cancer cell lines (9/9) and 70.83% (85/120) of primary lung tumor tissues compared with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 43 publications
0
85
1
Order By: Relevance
“…DNA methylation is a common mechanism of tumor suppressor gene inactivation and tumorigenesis . Recent studies have demonstrated that a series of methylation‐silenced tumor suppressor genes are associated with lung cancer progression …”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is a common mechanism of tumor suppressor gene inactivation and tumorigenesis . Recent studies have demonstrated that a series of methylation‐silenced tumor suppressor genes are associated with lung cancer progression …”
Section: Introductionmentioning
confidence: 99%
“…The representatives of the group F of SOX proteins are the proteins SOX7, SOX17 and SOX18, jointly involved in the development of the cardiovascular and lymphatic systems during the embryogenesis process (27,28). Since the main characteristic of these proteins is their high homology, they are able to take over each other's functions, as demonstrated in a mouse model where the inhibition of the SOX18 gene expression resulted in an increased expression of the SOX7 and SOX17 gene (29).…”
Section: Group F Of Sox Proteinsmentioning
confidence: 90%
“…On the other hand, in cancer, the majority of TSGs are silenced and their reactivation can have a beneficial impact on cell cycle repression and apoptosis and exert therapeutic effects 404142 . Because it has been demonstrated that hypermethylation of promoter regions of TSGs is one of the major epigenetic alterations in lung cancer development 434142 , treating the respiratory epithelium with demethylating agents would help tip the scales toward tumor suppression. Further detailed investigations however, should be pursued to uncover whether Aza can hypomethylate the promoter of oncogenes in cancers and its impact on potential cancer development.…”
Section: Discussionmentioning
confidence: 99%